Experimental Investigation of {99m}Тс-Nanotech Used for Lymph Nodes Visualization - Sinilkin I. G. Ivan Gennadjevich; Chernov V. I. Vladimir Ivanovich; Titskaya А. А. Anna Aleksndrovna; Zelchan R. V. Roman Vladimirovich; Daneykina (Daneikina) N. V. Natalia Viktorovna (Radiation Technologies in Medicine, 2015)
Title screen